The importance of nursing in the care of children victim of sexual violence (Research, Society and Development, 2024)
Introduction: This study focuses on the vital importance of nursing in the care of children victims of sexual violence. In a challenging ethical, legal, and psychosocial context, the research highlights the need for an interdisciplinary approach to ensure comprehensive and effective care. Objectives: The objective of this article is to propose specific strategies to enhance the performance of professionals, highlighting the essential sensitivity and empathy when dealing with this delicate reality. Methodology: It encompasses a comprehensive literature review and case analysis, grounding the understanding of the challenges faced in assisting these children. Results: The studies revealed a predominance of qualitative approaches, with about 70% descriptive studies and 30% divided between cross-sectional and quantitative studies. The essential role of nursing in the care of children victims of sexual violence was highlighted, emphasizing the importance of early identification, sensitive approach, and interdisciplinary work to ensure the physical and emotional recovery of the victims. Conclusions: They highlight the urgency of specialized care and the need for awareness of the child's vulnerability in the face of sexual violence. This work contributes by promoting a compassionate and innovative approach, highlighting nursing as a fundamental piece in this sensitive scenario. Thus, the research aims to raise awareness of the importance of the nursing role in the context of child sexual violence, aiming at promoting effective and child-centered interventions.